La recomposition des savoirs au Maghreb à l’époque de la coopération - Jean-Robert Henry (L’Année du Maghreb)
The period of cooperation was not only stimulating individually and collectively for the many French and North Africans who lived between the mid-fifties and the late 1970s, it was an important time to challenge intellectual certainties and reformulate the scientific vision of the world. In the social sciences, it was an age of deconstruction and reconstruction of colonial knowledge, for inventing north-south relations, a time for reconfiguring the concept of cultural space and a time of intense multidisciplinarity. The desire for a renewed approach did not avoid caricature and dogmatism. Indeed, a theoretical universalism intended as replacement for discriminating colonialist discourse, vested itself in a more or less modernized Marxist vulgate of the economy, sociology, linguistics, law, anthropology. More generally, the mission of serving development was conceived in new world time as somehow an echo of the civilizing mission of the past. Yet, despite its limitations and its excesses, “cooperation” may have facilitated the advent of decolonization such that half a century later, European policy was not able to place its relations with the South into a context dominated by cultural reductionism. It is for this reason, without concession to nostalgia or sentiment, that it is useful to revisit the experience and examine the record of cooperation in the social sciences to draw what lessons there may be.